A prospective case-control study on the efficacy of subcutaneous suction drainage in reducing surgical site infections following laparotomy - Sahoo, Deepak Kumar; Das, Deepak Kumar; Nayak, Snigdha; Lenka, Biranchi Narayan (International Journal of Research in Medical Sciences, 2026)
Background: Surgical site infections (SSIs) are one of the major postoperative complications and their management still remains to be a gruelling task. The worldwide incidence of SSI ranges between 0.5 and 15%, but in India it shows a significant increase of about 23 to 38%. The placement of suction drains in surgical wounds has proved to be quite promising especially in emergency laparotomies. The objective of this study was to compare the incidence of SSIs in abdominal surgical wounds with subcutaneous suction drains versus those where drains were not used. Methods: This is a case-control study of 60 patients undergoing midline exploratory laparotomy surgeries admitted in the gastrosurgery and general surgery department of Hitech Medical college and Hospital, Bhubaneswar. Among them, closed subcutaneous drain was placed before the skin closure for every alternate patient and for the others no subcutaneous drain was placed. The patients for whom subcutaneous drain were placed were considered as cases while the other group of patients were considered as control group. Results: The patients in the case group had lower incidence of SSI compared to the control group. When compared between the emergency and elective cases, the emergency cases showed higher propensity for SSI. Conclusions: Subcutaneous suction drains have proved to be safe and effective in preventing SSIs in abdominal surgeries, especially in emergency and colorectal surgeries.